Riverine Li isotope fractionation in the Amazon River basin controlled by the weathering regimes. (1st September 2015) - Dellinger, Mathieu; Gaillardet, Jerome; Bouchez, Julien; Calmels, Damien; Louvat, Pascale; Dosseto, Anthony; Gorge, Caroline; Alanoca, Lucia; Maurice, Laurence
Abstract: We report Li isotope composition (δ 7 Li) of river-borne dissolved and solid material in the largest River system on Earth, the Amazon River basin, to characterize Li isotope fractionation at a continental scale. The δ 7 Li in the dissolved load (+1.2‰ to +32‰) is fractionated toward heavy values compared to the inferred bedrock (−1‰ to 5‰) and the suspended sediments (−6.8‰ to −0.5‰) as a result of the preferential incorporation of 6 Li into secondary minerals during weathering. Despite having very contrasted weathering and erosion regimes, both Andean headwaters and lowland rivers share similar ranges of dissolved δ 7 Li (+1.2‰ to +18‰). Correlations between dissolved δ 7 Li and Li/Na and Li/Mg ratios suggest that the proportion of Li incorporated in secondary minerals during weathering act as the main control on the δ 7 Lidiss across the entire Amazon basin. A "batch" steady-state fractionation model for Andean and lowland rivers satisfactorily reproduces these variations, with a fractionation factor between weathering products and dissolved load ( α sec - dis ) of 0.983 ± 0.002. Two types of supply-limited weathering regimes can be identified for the lowlands: "clearwaters" with dominant incorporation of Li in secondary minerals, and "black waters" (e.g., Rio Negro) where dissolution of secondary minerals enhanced by organic matter produces low δ 7 Li. Apart from the black waters, the δ 7 Li of Andean and lowland rivers is negatively correlated to the denudation rates with the lowest δ 7 Li corresponding to the rivers having the highest denudation rates. In contrast, the main tributaries draining both the Andes and the lowlands have higher δ 7 Li compared to other rivers. We propose that part of the dissolved Li derived from weathering in the Andes is re-incorporated in sediments during transfer of water and sediments in floodplains and that this results in an increase of the dissolved δ 7 Li along the course of these rivers. Unlike other rivers, the dissolved δ 7 Li in the main tributaries is best described by a Rayleigh fractionation model with a fractionation factor α sec - dis of 0.991. Altogether, the control imposed by residence time in the weathering zone and floodplain processes results in (i) a non-linear correlation between dissolved δ 7 Li and the weathering intensity (defined as W/D) and (ii) a positive relationship between the dissolved Li flux and the denudation rate. These results have important implications for the understanding of past ocean δ 7 Li and its use as a paleo weathering proxy.